On the Maintenance of Expectations in Major Depression – Investigating a Neglected Phenomenon - Kube, Tobias; Rief, Winfried; Glombiewski, Julia A. (Frontiers in Psychology, 2017)
In this perspective paper, we suggest that among patients suffering from major depressive disorder (MDD), dysfunctional expectations are maintained despite experiences that are contrary to these expectations. Surprisingly, this persistence of expectations in MDD has not yet been addressed by empirical studies. We argue that it is worthwhile to investigate this phenomenon with the aim of improving the treatment of MDD, and we provide a theoretical framework for understanding it. It is hypothesized that the persistence of expectations is primarily due to a process called immunization. That is, people experiencing depressive symptoms may cognitively reappraise the contradictory experience such that expectations do not need to be changed. There may be two mechanisms underlying this immunization: (1) the experience in the expectation-violating situation is considered to be an exception; or (2) the credibility of the information gained from the experience is called into question. Moreover, the maintenance of expectations may be particularly persistent if a person’s expectations reflect his or her self-concept, as self-concept has been shown to be associated with future expectations. To empirically examine the hypothesized maintenance of expectations in MDD, we propose an experimental approach which could provide important implications for the treatment of MDD within cognitive behavioral therapy. We suggest that psychological interventions such as behavioral experiments should more rigorously focus on patients’ appraisal of expectation-violating experiences in order to prevent immunization processes. Therapists should continuously examine whether patients’ expectations were modified and should address the reasons for the maintenance of expectations.